Analysis of small extracellular vesicles from dried blood spots - Rikke Bæk; Jenni Kathrine Sloth; Mohammad Mehedi Hasan; Getnet Midekessa; Getnet Midekessa; Malene Møller Jørgensen; Malene Møller Jørgensen (Frontiers in Medical Technology)
This protocol paper describes how to extract small extracellular vesicles (sEVs) from dried blood spots (DBS). The methodology is described in detail and offers further evidence that the extracted particles are sEVs using western blotting (anti-CD9, CD63 and CD81) and fluorescence nanoparticle tracking analysis (fNTA). In addition, we present evidence that approximately 40% of the sEVs were recovered from DBS compared with EVs analyzed from plasma directly. The protocol proves to be robust, reliable and displays very interesting performances even after several weeks (up to 3 weeks) of storage of the DBS when analyzing the sEVs using protein microarray for the presence of the markers CD9, CD63, CD81, EpCAM, Flotilin-1, CD62E/P, CD142 and CD235a. These findings have important implications for using sEVs as future potential diagnostic tools by supporting the validity of less-invasive methods that can be implemented within vulnerable populations or in the field.